My seven book - Moncure, Jane Belk (Elgin, Ill : Child's World, 1985)
Little Seven introduces concept of "seven" by interacting with seven variety of things, some of which are grouped and regroupd to demonstrate adding and subtracting.
Keywords: Seven (The number) -- Juvenile literature; Number concept; Counting